Pengaruh Pengalaman Belanja Online Dan Nilai Yang Dirasakan Terhadap Niat Beli Kembali Secara Online - Anastasya Sinambela, Ella (CV. Multi Kreasi Media, 2024)
The development of online shopping applications gives people the choice to shop online or in person. Online shopping, which can be done anywhere, makes people choose to shop online. Competition in shopping applications requires manufacturers to increase consumers' repurchase intentions online. This research aims to determine the influence that consumer shopping experience and perceived value have on online repurchase intentions. The sample for this research was 100 respondents obtained by purposive sampling. Data analysis was carried out using multiple linear regression. The research results show that consumer shopping experience and perceived value are proven to have an impact on online repurchase intentions.